Language identification: how to distinguish similar languages? - Ljubešić, Nikola; Mikelić, Nives; Boras, Damir (2007)
The goal of this paper is to discuss the language identification problem of Croatian, language that even state-of-the-art language identification tools ﬁ nd hard to distinguish from similar languages, such as Serbian, Slovenian or Slovak language. We developed the tool that implements the list of Croatian most frequent words with the threshold that each document needs to satisfy, we added the specific characters elimination rule, applied second-order Markov model classification and a rule of forbidden words. Finally, we built up the tool that overperforms current tools in discriminating between these similar languages.
Projekt MZOS
ENG